Language Assessment For Young Learners - Sumarni Sumarni (Jurnal Visi Ilmu Pendidikan, 2016)
Teaching English in Asia typically dominated by teachers and textbooks based. Even worse, teaching English for young learners is generally a matter of vocabularies memorization. The teaching focuses on short-term purposes, those are testing purposes. In fact, in teaching English, the assessment should focus on the function of the language itself. Those teaching styles might be caused by short-term purpose of teaching English: focuses on knowledge and memorization for testing purposes rather than communicative competence. Therefore all the teaching efforts focused on answering the tests while the primary function of learning English is being ignored. Memorizing vocabularies is general activities in teaching of English in primary level.  Thus to avoid such short-term purpose learning, a well and careful designed assessment should put into consideration in teaching English for young learners. Consequently the teaching-learning process will focus on authentic use of language. For those reason, authenticity in the assessment is a major consideration. Key words: Teaching, young learners, assessment, authenticity